Q: What is 2 plus a2?

Write your answer...

Submit

Related questions

sqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*a

a2+b2+c2=x2+y2+z2 divide each side by 2 (a2+b2+c2)/2=(x2+y2+z2)/2 a+b+c=x+y+z

(a2 + 2)(b + 3)

No. If you expand (a + b)2 you get a2 + 2ab + b2. This is not equal to a2 + b2

a3 + b3 + c3 + 2(a2)b + 2(b2)c + 2(a2)c + 2ab2 + 2(c2)b +abc

int x = 2 * (a + b);

( a2 ) ( a2+1 )

(a2 + a + a2) = (2a2 + a) = a (2a + 1)

a3 - 2a2 + 4a - 8 = a2(a - 2) + 4(a - 2) = (a - 2)(a2 + 4)

a2+30a+56=0 , solve for a Using the quadratic formula, you will find that: a=-2 , a=-28

(a2 + 5a + 6)/(a - 2) = (a + 2)*(a 3)/(a - 2) which cannot be simplified further. It can, however be written as (a2 - 2a + 7a - 14 + 20)/(a - 2) which is (a + 7) + 20/(a - 2)

a2 - 4a + 4

a2/2

a2 + a2 = 2a2

a2 + -5a2 - a2 - a = a2 - 5a2 - a2 - a = a2 - 6a2 - a = -5a2 - a

a2+9a+20 = (a+4)(a+5) when factored

1 by 2

a2+2a2b+2ab2+b2

a2 - 6a + 9 = a2 - 3a - 3a + 9 = a(a - 3) - 3(a - 3) = (a - 3)*(a - 3) = (a - 3)2

5a3-45a=-2a2+18 5a(a2-9)=-2(a2-9) 5a=-2 a=-2/5

A42a

2 a2 is a monomial, not a binomial but 2 + a2 is a binomial, so is 2 - a2 .

a≠ 0,LCD = a33/a + 2/a2 - 1/a3= (3/a)(a2/a2) + (2/a2)(a/a) - 1/a3= 3a2/a3 + 2a/a3- 1/a3= (3a2 + 2a -1)/a3

(a+b+c) 2=a2+ab+ac+ba+b2+bc+ca+cb+c2a2+b2+c2+2ab+2bc+2ca [ ANSWER!]

(A+B)2 = (A+B).(A+B) =A2+AB+BA+B2 =A2+2AB+ B2 So the Answer is A + B the whole square is equal to A square plus 2AB plus B square. Avinash.